2017
DOI: 10.1186/s12879-017-2254-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mortality rates and causes of death in a population-based cohort of persons living with and without HIV from 1996 to 2012

Abstract: BackgroundNon-HIV/AIDS-related diseases are gaining prominence as important causes of morbidity and mortality among people living with HIV. The purpose of this study was to characterize and compare changes over time in mortality rates and causes of death among a population-based cohort of persons living with and without HIV in British Columbia (BC), Canada.MethodsWe analysed data from the Comparative Outcomes And Service Utilization Trends (COAST) study; a retrospective population-based study created via linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 35 publications
(41 reference statements)
3
48
1
2
Order By: Relevance
“…For instance, in European and American studies, HIV patients tend to be diagnosed and initiated on ART much earlier with potential less mortality on ART receipt. However, even with the present differences in mortality rate, the clinical message remains significantly similar that, despite the use of ART, the mortality among HIV-positive patients is comparatively higher than the general population in both developed and developing countries with comparable timing of these deaths in most series [21, 22]. For instance, in one study from Ethiopia, where 10.0% of patients on ART died in 6 years of follow-up, it was found that 62.9% of the reported deaths occurred in the first year of ART [23], while in a study by Johannessen et al from Manyara, Tanzania, it was indicated that 72.7% of the reported deaths occurred within the first 12 months of ART initiation [20].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in European and American studies, HIV patients tend to be diagnosed and initiated on ART much earlier with potential less mortality on ART receipt. However, even with the present differences in mortality rate, the clinical message remains significantly similar that, despite the use of ART, the mortality among HIV-positive patients is comparatively higher than the general population in both developed and developing countries with comparable timing of these deaths in most series [21, 22]. For instance, in one study from Ethiopia, where 10.0% of patients on ART died in 6 years of follow-up, it was found that 62.9% of the reported deaths occurred in the first year of ART [23], while in a study by Johannessen et al from Manyara, Tanzania, it was indicated that 72.7% of the reported deaths occurred within the first 12 months of ART initiation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Combination antiretroviral therapy (cART) has dramatically improved the survival and quality of life for people living with HIV . A growing proportion of patients are over the age of 50 years, and by the end of 2013, over four million individuals older than 50 years were living with HIV infection worldwide .…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported in high-income countries where cART has been available for the past 2 decades. 4,5,7,9 Such studies also show that death is increasingly attributed to non-AIDSrelated causes, including non-AIDS-defining malignant disease, 5,6 cardiovascular disease 6 and liver disease, 4,6 even as rates of death from these causes decline. 7,8 In the current study, in 1995-1999, age differences in HIV/AIDS-associated mortality were modest, likely because cART was not yet in widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…Research chronic liver disease (in particular due to hepatitis B and C), cardiovascular disease and suicide were also observed, 7,8 which represents new trends in the primary causes of death in people with HIV infection.…”
Section: Openmentioning
confidence: 99%